2017
DOI: 10.1186/s12886-017-0649-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous hemorrhage and Rhegmatogenous retinal detachment that developed after botulinum toxin injection to the extraocular muscle: case report

Abstract: BackgroundThe authors report a case of a rare complication that occurred after botulinum toxin injection to the extraocular muscle, which was easily overlooked and successfully corrected by surgery.Case presentationA 34-year-old female patient visited our clinic for diplopia and ocular motility disorder after removal of an epidermoid tumor of the brain. At her initial visit, her best-corrected visual acuity (BCVA) was 20/20 for both eyes. An alternate cover test showed 45 prism-diopter esotropia and 3 prism-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Scleral perforation has only been reported in two cases after botulinum toxin injection without electromyographic guidance [ 24 , 25 ]. This is also extremely rare after botulinum toxin injection with electromyographic guidance [ 26 , 27 ], with an incidence of 0.002% [ 15 ]. In rabbits, Paik et al [ 28 ] found no different morphologic changes in the extraocular muscle fiber layers between direct intramuscular injection and subtenon injection of botulinum toxin.…”
Section: Discussionmentioning
confidence: 99%
“…Scleral perforation has only been reported in two cases after botulinum toxin injection without electromyographic guidance [ 24 , 25 ]. This is also extremely rare after botulinum toxin injection with electromyographic guidance [ 26 , 27 ], with an incidence of 0.002% [ 15 ]. In rabbits, Paik et al [ 28 ] found no different morphologic changes in the extraocular muscle fiber layers between direct intramuscular injection and subtenon injection of botulinum toxin.…”
Section: Discussionmentioning
confidence: 99%
“…Some transient ocular complications, such as ptosis, diplopia and glaucoma, have been reported due to periocular and extraocular BTA injection 3 . Rarely, vitreous haemorrhage and restrictive optic neuropathy have also been described 3,4 .…”
Section: Discussionmentioning
confidence: 99%
“…Some transient ocular complications, such as ptosis, diplopia and glaucoma, have been reported due to periocular and extraocular BTA injection 3 . Rarely, vitreous haemorrhage and restrictive optic neuropathy have also been described 3,4 . Only one study has shown that transient vision loss due to retinal ischaemia may occur after cosmetic BTA injection in the masseter muscle 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Periorbital botulinum toxin injection can cause mydriasis of the pupil, resulting in acute angle closure attack. Cases have been reported in which the botulinum toxin was improperly injected into the vitreous cavity of a patient receiving treatment to the right medial rectus, resulting in increased intraocular pressure, decreased visual acuity and retinal detachment [ 18 ]. Apart from periorbital complications, other aesthetic side effects associated with botulinum toxin injection for forehead horizontal lines are the exaggeration of wrinkles, brow ptosis, “Mephisto sign”, and periorbital edema.…”
Section: Transient and Benign Side-effectsmentioning
confidence: 99%